2020
DOI: 10.7554/elife.51992
|View full text |Cite
|
Sign up to set email alerts
|

The speed of GTP hydrolysis determines GTP cap size and controls microtubule stability

Abstract: Microtubules are cytoskeletal polymers whose function depends on their property to switch between states of growth and shrinkage. Growing microtubules are thought to be stabilized by a GTP cap at their ends. The nature of this cap, however, is still poorly understood. End Binding proteins (EBs) recruit a diverse range of regulators of microtubule function to growing microtubule ends. Whether the EB binding region is identical to the GTP cap is unclear. Using mutated human tubulin with blocked GTP hydrolysis, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
107
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(128 citation statements)
references
References 54 publications
18
107
2
1
Order By: Relevance
“…A closer examination of MT pauses revealed that these events in control cells were significantly more long-lived: 8.3 ± 5.6 s (mean ± SD) compared to those in KIF21B-KO cells: 4.1 ± 2.2 s (KO #1, mean ± SD) and 4.3 ± 2.4 s (KO #2, mean ± SD) ( Figure 4F , Figure 4—figure supplement 1A ). We note that these pause durations are longer than those observed with EB3-mCherry ( Figure 3I ), because the latter labels growing MTs, and its signal is gradually lost when MT plus ends switch to pausing and lose the GTP cap that EB3 labels ( Roostalu et al, 2020 ). Overall, these data indicate that in T cells, KIF21B acts as a factor that inhibits MT growth and induces pausing and catastrophes.…”
Section: Resultsmentioning
confidence: 85%
“…A closer examination of MT pauses revealed that these events in control cells were significantly more long-lived: 8.3 ± 5.6 s (mean ± SD) compared to those in KIF21B-KO cells: 4.1 ± 2.2 s (KO #1, mean ± SD) and 4.3 ± 2.4 s (KO #2, mean ± SD) ( Figure 4F , Figure 4—figure supplement 1A ). We note that these pause durations are longer than those observed with EB3-mCherry ( Figure 3I ), because the latter labels growing MTs, and its signal is gradually lost when MT plus ends switch to pausing and lose the GTP cap that EB3 labels ( Roostalu et al, 2020 ). Overall, these data indicate that in T cells, KIF21B acts as a factor that inhibits MT growth and induces pausing and catastrophes.…”
Section: Resultsmentioning
confidence: 85%
“…A cap of GTP-tubulin at the end of a growing microtubule is widely accepted as the determinant of microtubule stability (Mitchison and Kirschner, 1984) (Drechsel and Kirschner, 1994) (Desai and Mitchison, 1997) (Duellberg et al, 2016) (Roostalu et al, 2020). The size of the GTP-cap is defined by the balance between the addition of new GTP-tubulin dimers to the growing microtubule end, and the hydrolysis of GTP to GDP within the microtubule polymer.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the precise conformational cycle, our results agree best with the view of GMPCPP-tubulin being one of the cap-stabilizing, expanded, and flexible conformations that are unlikely to be preceded by stiffer and compacted ones. Perhaps a more promising approach toward ultimately resolving this issue in future structure determination efforts would be to use knowledge-based point mutations that selectively uncouple the tubulin conformational and GTPase cycles [51,52].…”
Section: Plos Computational Biologymentioning
confidence: 99%